2008
DOI: 10.1109/tit.2008.921684
|View full text |Cite
|
Sign up to set email alerts
|

Perfectly Secure Steganography: Capacity, Error Exponents, and Code Constructions

Abstract: An analysis of steganographic systems subject to the following perfect undetectability condition is presented in this paper. Following embedding of the message into the covertext, the resulting stegotext is required to have exactly the same probability distribution as the covertext. Then no statistical test can reliably detect the presence of the hidden message. We refer to such steganographic schemes as perfectly secure. A few such schemes have been proposed in recent literature, but they have vanishing rate.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 40 publications
0
72
0
Order By: Relevance
“…In this scenario it has already been shown that the embedder can communicate completely undetectably at a nonzero (linear) rate by preserving all the statistics of the covers [1]. However, no such system, for embedding in real-world cover media, has ever been constructed.…”
Section: Stegosystems With Imperfect Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this scenario it has already been shown that the embedder can communicate completely undetectably at a nonzero (linear) rate by preserving all the statistics of the covers [1]. However, no such system, for embedding in real-world cover media, has ever been constructed.…”
Section: Stegosystems With Imperfect Informationmentioning
confidence: 99%
“…1 (1). Write X for the number of 1 bits in the cover stream, and Y for the number in the object to be classified.…”
Section: Proof Of Theorem 2 (1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Information theoretic quantities, particularly the Kullback-Leibler (KL) divergence between cover and stego distributions, can bound the secure embedding capacity [1,2] but, naturally, they require knowledge of these distributions and this seems infeasible for digital media. Whilst information theory has produced interesting results about the rate of capacity growth [3,4], these do not specify concrete payload sizes for particular, real-world, covers.…”
Section: Introductionmentioning
confidence: 99%